Changes in the running motion with fatigue during middle-distance running - Kadono, H.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to investigate the changes in the running motion with fatigue during middle-distance running and get the knowledge about how to maintain the running velocity under fatigued condition by comparing the running motion with fatigue to it with no fatigue. The step length at the fatigued was shorter than the non-fatigued, on the other hand the step frequency was larger than the non-fatigue. The peak ankle joint plantar flexion torque and positive torque power of the support leg at the fatigued were smaller than the non-fatigued, as well as the peak and averaged vertical GRFs. The hip joint torque and power of the recovery leg at the fatigued were significantly larger than the non-fatigued. It is appropriate for maintaining the running velocity to move the recovery leg quickly and increase the step frequency under fatigued condition.